A DESCRIPTIVE STUDY ON ALTRUISM OF GOOD DINOSAUR MOVIE - Mellinio, Stephano Trie; Regina, Regina; Suhartono, Luwandi (Jurnal Pendidikan dan Pembelajaran Khatulistiwa (JPPK), 2023)
This research aims to describe the dominant altruism values of the Good Dinosaur movie and investigate the lessons of the Good Dinosaur movie for learning. The form of this research is qualitative research. The method used is the descriptive method. The technique of data collecting was the documentation technique. The technique of data analysis was descriptive analysis. The tools for data collecting were observation tables and documents. The result of this research showed there were 38 utterances of altruism values in Good Dinosaur Movie. Altruistic values appeared 9 times. Altruistic behavior appeared 18 times. Altruism empathy appeared 11 times. The dominant altruism in Good Dinosaur Movie was altruistic behavior. The lesson that can be learned from that movie was to be humble to everyone. It should be supported by other people in whatever situation. Do not ever underestimate other people. Helping people without getting a reward is an important thing in life.